Visualization of bubble coalescence in bubble chains rising in a liquid metal. (August 2018) - Keplinger, O.; Shevchenko, N.; Eckert, S.
Highlights: X-ray radiography combined with high-speed video imaging was used to visualize the processes of bubble interaction in opaque liquid metals. The processes of bubble approach, collision and coalescence were found to proceed in a qualitatively similar way as for the case of water or highly viscous fluids. The observations indicate that the turbulent flow in the immediate vicinity of the bubbles has an important influence on whether coalescence occurs or not. Abstract: Bubble coalescence in liquid metals was studied by considering the case of a bubble chain rising in the eutectic alloy GaInSn. The experiments were performed in a flat vessel with a rectangular cross section. High frame-rate X-ray radiography was used for visualizing the interaction between the bubbles. Essential process parameters such as bubble sizes, bubble shapes, velocities and distance of their closest approach are obtained from image processing. Different coalescence schemes occurring inside the bubble chain are discussed and demonstrated. The results are compared to collision cases where the bubbles bounce off each other. The material properties of the liquid metal differ significantly from those of water or other transparent fluids. In particular, the low viscosity, the high density and the high surface tension result in low values of the Mo number, Mo ≈ 2 × 10 −13 and high Reynolds numbers of Re ∼ 10 4 . Nevertheless, the process of bubble approach, collision and coalescence was found to proceed in a qualitatively similar way as reported by previous studies for the case of water or highly viscous fluids. From the analyzed data, it was difficult to define a quantitative criterion that would allow predicting whether a pair of colliding bubbles would coalesce or bounce off. The observations indicate that the turbulent flow in the immediate vicinity of the bubbles has an important influence on whether coalescence occurs or not.